Prevalence of female reproductive tract cancer in a teaching hospital of Rohtas District, Bihar, India - Kumar, Rajendra (International Journal of Research in Medical Sciences, 2018)
Background: The organs of female reproductive tract are involved by various ailments up to malignancy and different types of malignancy involve these organs causing unbearable symptoms to the patient and harassment to the affected family. However, the incidence varies, and cervical carcinoma is more common in Asian countries even after use of screening tests in specialized hospitals. The study was undertaken to assess the prevalence of malignancy of these organs among females in this location of Rohtas district of Bihar. Methods: A study of female reproductive system was done retrospectively for a period of 3 years and the suspected 1409 patients underwent operative procedures and tissues were microscopically examined of haematoxylin and eosin stained slides by conventional methods. Results: Of the 58 malignant cases of female reproductive organs, cervical carcinoma emerged as the commonest with 56.9%, followed by endometrial carcinoma (22.4%), and ovarian cancers (15.5%). The vaginal and vulval cancers were found to be the lowest with 3.4% and 1.7% cases respectively. Conclusions: The squamous cell carcinoma (67%) was the commonest malignancy of cervical cancers whereas adenocarcinoma (85%) was the most common involvement of endometrial carcinoma histologically diagnosed.